Canadian Child Benefits: Behavioral Consequences, Income Adequacy and Alternatives - Shelley Phipps (Luxembourg Income Study (LIS), 1993)
Uses LIS data to assess three dimensions of the new Canadian child benefit system: how the earned-income supplement will affect labor supply, the existence and consequences of lags between the receipt of benefits relative to income loss, and finally benefit levels are demonstrated to be lower than necessary to support a child.
Keywords: 330